Optimal integration of D-STATCOM in distribution grids for annual operating costs reduction via the discrete version sine-cosine algorithm (2022)
This paper deals with the problem of the optimal placement and sizing of distribution static compensators (D-STATCOM) in electrical distribution networks to reduce the total annual operative costs associated with the total costs of energy losses added with the investment costs in D-STATCOM. The metaheuristic sine-cosine optimization algorithm determines nodes with the location and optimal sizes of the D-STATCOM. A discrete-continuous codification represents the decision variables, where the discrete part is entrusted with the best candidate nodes selection. The continuous part deals with the optimal sizes assigned to the D-STATCOM. Numerical results in the IEEE 33- and IEEE 69-bus systems demonstrate the effectiveness of this approach since it helps to minimize the total grid operation costs compared with the solution of the mixed-integer nonlinear programming model in GAMS. All the numerical validations are carried out in the MATLAB programming environment. © 2022 The Authors